Pengaruh Nilai Tukar (Kurs) Dan Tingkat Suku Bunga Terhadap Return Saham Syariah Dengan Menggunakan Variabel Intervening Indes Saham Syariah Indonesia (ISSI). (Study Kasus Pada Setor Property Dan Real Estate Periode Desember 2015-Mei 2016) - Hanita Yuniati (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
ABSTRACT The purpose of this study is to analyze how much influence the exchange rate (exchange rate), the interest rate on the return of Sharia shares with Indonesia Sharia Shares Index (ISSI) as intervening variable on property sector and real estate period December 2015-May 2016 period. Population in this research is syariah stock listing in Bursa Efek Indonesia (BEI) in property sector and Real Estate period december 2015 -Mei 2016. Method of sampling purposive sampling. Data analysis used multiple linear regression technique with F test, T test, path analysis test and assumption test..The result shows that the exchange rate has a significant positive effect on Indonesia Sharia Sharia Index (ISSI), the significant positive effect on Indonesian Sharia Index (ISSI) and Indonesia Sharia Shares Index (ISSI) has a significant positive effect on Sharia Stock Return amount. The exchange rate with the mediation of Indonesia Sharia Shares Index (ISSI) has a significant positive effect on Sharia Return Shares and interest rate with the Sharia Index of Indonesian Sharia Securities has a positive effect on Sharia Stock Return. Together the effect of exchange rate, interest rate and Sharia Stock Index of Indonesia (ISSI) have a significant positive effect on Sharia Return Shares. Keywords:Exchange Rate, Interest Rate, Sharia Stock Index of Indonesia (ISSI) and Return of Sharia Share